OPTIMALISASI PERLINDUNGAN HUKUM TERHADAP KORBAN DALAM TINDAK PIDANA LINGKUNGAN - Satriyana, Arie Rizky; Ramada, Diandra Preludio (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Indonesia is a country rich in natural resources, yet it continues to face various complex environmental problems. Environmental degradation is not only caused by natural factors but also by irresponsible human actions. In legal terms, environmental protection is regulated under several laws, including Law Number 32 of 2009. However, victims of environmental crimes often do not receive optimal legal protection. The Indonesian criminal justice system remains offender-oriented, placing greater emphasis on the rights of perpetrators rather than victims. As a result, victims’ rights are often neglected during legal proceedings. This research aims to examine the existing regulations regarding legal protection for victims in Indonesia and to propose efforts for optimizing such protection, particularly in the context of environmental crimes. The research uses a normative juridical method with a statutory and literature approach. The results of this study are expected to contribute to the improvement of a legal system that is more victim-oriented, especially in environmental crime cases.